Psychometrics of the Spanish Version of the Screen for Adult Anxiety Related Disorders (SCAARED) - Sánchez-Cueva, Sarah; Alonso-Esteban, Yurena; Sánchez-Cueva, Patricio; Birmaher, Boris; Alcantud-Marín, Francisco (Frontiers in Psychiatry, 2021)
Objectives: To translate and validate the Screen for Adult Anxiety Related Disorders (SCAARED) questionnaire into Spanish. Method The original SCAARED was translated into Spanish and administered to a non-clinical sample of 131 university students (92.4% women, mean age 22 years) in Valencia, Spain. To assess the concurrent validity of the SCAARED, the Depression, Anxiety and Stress Scale -21(DASS) and the Beck's Anxiety Inventory (BAI) were also administered. Test-retest reliability was evaluated two weeks after the first administration. Results: The internal consistency of SCAARED was high (α = .91) and the stability of the measurement was also high (test-retest .81). The results of the Exploratory Factor Analysis showed four factors comparable to the original SCAARED (generalized anxiety disorder, social phobia disorder, panic disorder, and separation anxiety disorder). The Area Under the Curve was excellent (0.88). Conclusions: The Spanish version of the SCAARED showed good psychometric properties comparable to the original SCAARED suggesting that it may be a useful instrument to screen for anxiety disorders in Spanish-speaking adult populations. Future studies are needed to replicate these findings in larger community and clinical samples